Effect of Compensation System on Employee Engagement in Fairtrade Horticultural Firms in Kenya - Margaret Kaathi Mwingirwa; Dennis Juma Okello; Hesbon N. Otinga; Daniel Kitonga (European Scientific Journal, ESJ, 2024)
While most people understand that engaged employees are often happier and more satisfied in their job, the main reason that engagement is now a focal point is because it leads to real business results. Emotional states are hard to understand and measure. Employees are becoming key business drivers for any organization. The objective of the study was to determine the effect of compensation system on employee engagement in Fairtrade horticultural firms in Kenya. A cross-sectional descriptive survey research design was adopted. The study targeted 17 fairtrade horticultural firms as unit of analysis and 5,600 employees as the unit of observation. The sample size was 373 respondents drawn from low level, middle level, and top-level management. The study relied mainly on primary data. The study adopted stratified and simple random sampling techniques. After the stratification of the respondents into strata, simple random sampling was adopted to pick up the respondents. The researcher used questionnaire as the research instrument. Descriptive and inferential analysis were computed using SPSS version 26. In order to analyze the relationship between the independent variables and the dependent variable the study used Regression analysis at 5% level of significance. The findings indicated that compensation system has a positive and significant effect on employee engagement in Fairtrade horticultural firms in Kenya. The study concluded that compensation system contributes significantly to the employee engagement in Fairtrade horticultural firms in Kenya. From the results, the study recommended the need for horticultural firm to strengthen their compensation system aspects. In particular, the firms should develop better compensation systems since they offer an incentive for personnel training and development which enhances efficiency within the firm.